Rebranding LPP TVRI Melalui Logo Baru - Asep Sugiarto; Febby Alpionita (Communicology: Jurnal Ilmu Komunikasi, 2019)
ABSTRACT Rebranding process undertaken by LPP TVRI through its creation of new logo has been undisclosed, specifically to millennials. This research aims to perceive the information about the objective, process, and as well to analyze the impact of rebranding process through the new logo. This research utilizes a main concept about rebranding process in accordance to Ahonen, M (2008) which comprises of four stages, namely analyzing, planning, implementation, and evaluation. The method used is descriptive qualitative research. The technique used is intrinsic study case supported by data collection technique by conducting an in-depth interview, observation, and literature study. One key interviewee and four other interviewees are chosen using purposive technique. The result of this research shows that the objective of rebranding of LPP TVRI by creating a new logo is to mobilize the public perception to a positive image of corporate identity. The new logo-rebranding attempt is consisted of four stages, first is analyzing to know the state of affair of the corporate. Second, it takes planning which ensues two strategies. They are re-positioning, which it used to be merely a single platform and turns out it becomes a media that unites the multiplatform, and re-design of TVRI logo with the assistance of DMID brand consultant service. Third, implementation that can be evidenced through a show called New Logo Launching TVRI. Fourth, it ends with evaluation which has not done completely yet. The aftermath of new logo-rebranding process is to create a betterment of TVRI image, escalates the rating and numbers of audience, performance, and public perceptions. The conclusion of this research is the implementation attempted by TVRI by launching a brand-new logo is inefficacious, it hasn’t reached to all levels of population. The suggestion offered by this research is TVRI to directly involve millennials as they are the main targets of the corporate brand acknowledgement. Other than that, corporate is advised to execute a publication strategy through social media with impressive and consistent contents. Keywords: Rebranding; Image; Logo